In Silico Analysis of miRNA in Type 2 Diabetes Mellitus and Colorectal Cancer: Molecular Connections and Biomarker Potential - Alexander Ryan Wihardja; Ana Lucia Ekowati; Ferbian Milas Siswanto (Journal of Urban Health Research, 2026)
Introduction: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by hyperglycemia caused by insulin resistance and impaired insulin secretion, affecting 537 million adults worldwide in 2021 and projected to reach 783 million by 2045. T2DM increases the risk of malignancies, particularly colorectal cancer (CRC). MicroRNAs (miRNAs), small non-coding RNAs regulating gene expression, have emerged as molecular links between T2DM and CRC through their roles in proliferation, apoptosis, metabolism, and insulin signaling. Shared pathways, including PI3K/AKT/mTOR and IGF-1 signaling, support common pathogenic mechanisms. Due to their stability and disease-specific expression, miRNAs represent promising biomarkers. This study employs an in silico bioinformatics approach to identify shared dysregulated miRNAs, predict their target genes, analyze relevant molecular pathways, and evaluate their regulatory roles connecting T2DM with CRC development. Methods: This study employed an in silico approach using miRNA expression data from GEO datasets (GSE262614, GSE185845, GSE115513, GSE156732), analyzed with R under the criteria |Log2FC| > 1 and p < 0.05. Differentially expressed miRNAs from each dataset were compared using a Venn diagram to identify consistently dysregulated miRNAs. Target gene prediction was conducted using miRTargetLink 2.0 and miRWalk, followed by validation with mRNA datasets GSE25724 and GSE44076. Pathway enrichment analyses were performed using GO and KEGG through ShinyGO and Enrichr Results:  Analysis revealed that hsa-miR-182-3p was the only miRNA consistently experiencing upregulation in both T2DM and colorectal cancer. From hsa miR-182-3p a total of 9 validated target genes were identified, and most of them are involved in MAPK, mTOR, cell cycle, and insulin signaling pathways which are key pathways implicated in both diseases. Conclusion: This study indicates that hsa-miR-182-3p may serve as a molecular mediator linking the pathophysiological mechanisms of T2DM, such as insulin resistance and hyperinsulinemia, with colorectal cancer tumorigenesis, and may hold potential as a biomarker.